COLLABORATIVE WRITING STRATEGY TO IMPROVE STUDENTS' ABILITY AND PARTICIPATION IN WRITING DESCRIPTIVE TEXTS - Saputra, Denny; Sutapa, Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this Classroom Action Research was to improve students’ ability and participation in writing descriptive text through Collaborative Writing Strategy. The research subjects were 38 students from 10 Social-A at Saint Paul Senior High School Pontianak. The researcher emphasized the practice of group discussion and peer-assessment among students. The study showed that the implementation of Collaborative Writing Strategy gave positive implication which effected on learning improvement. Activities in the strategy improved students’ ability and participation in writing descriptive text. Group discussion and peer assessment helped students to generate, organize, and develop their ideas well after working with their group collaboratively. Collaborative Writing Strategy also encouraged students to get engaged more in teaching learning activities. Moreover, students also improved their writing score, which indicated that learning process have run well and have improved individual performance.         Keywords: Collaborative Writing, Descriptive Text, dan  Writing Ability